Crisis Response and Resilience to Systemic Shocks : Lessons from IEG Evaluations - Independent Evaluation Group (World Bank, Washington, DC, 2017)
During the past decade, the Independent Evaluation Group (IEG) evaluated the World Bank Group’s response to systemic shocks and its efforts to help build resilience in response to shocks such as the food crisis of 2007–08, the global financial crisis of 2008–09, natural disasters, climate change, and pandemics. These evaluations examined the response to each of these different shocks separately. This study examines the evaluations and learning products to draw general lessons from the experience that can help strengthen future support to countries’ resilience-building efforts.